The impacts of instructional media on the concept mastery of Merapi ecosystem succession - Rio Christy Handziko; I Gusti Putu Suryadarma (Universitas Ahmad Dahlan, 2021)
This research is focused on the use of different instructional media in learning activities. The aims of this research were to determine the impacts of different instructional media on students learning achievements, to investigate the values of significant difference among the used instructional media, and to investigate the equity distribution of learning outcomes in each class, with experimental research class design. The data collected from class with photographs and with videos as the instructional media, each class consists of 30 students. Then, the data were compared with three classes that used real objects as the instructional media. These classes consist of 29, 39, and 46 students. The research instruments to measure students learning achievements were tested for their validity and reliability with Quest Program. Normality test was carried out using Shapiro-Wilk, and homogeneity test used ANOVA. Then the analysis data of learning outcomes was administered using Kruskal-Wallis. The results show that the three classes which used real objects lead to better learning outcomes and smaller standard deviation value which shows the evenness of students learning achievements. Therefore, real objects have positive effects on student learning achievements in the ecosystem succession learning materials. The implication of this research is biology learning outcomes will be better if you use biology objects directly.